Human Stem Cell-Derived Neurospheroids and a Multi-Assay Strategy Provide Brain Cytotoxicity New Insights from ADB-FUBIATA Exposure - Uliana De Simone; Carlo Alessandro Locatelli; Francesca Caloni; Davide Lonati; Luciana Alessandra Russo; Teresa Coccini (Neurotoxicity Research, 2026)

Effects of Enniatin B1 on differentiated Caco-2 human intestinal cells in vitro - Giulia Ranaldi; Mirko Bertazzo; Barbara Guantario; Leon J Spicer; Francesca Caloni (Mycotoxin Research, 2026)

Novel miniaturized exposure to evaluate the toxicity of Enniatin B1 on Daphnia magna - Beatrice De Felice; Simona Mondellini; Mirko Bertazzo; Marco Parolini; Francesca Caloni (Environmental Toxicology and Pharmacology, 2025)

Guar gum as a microbially degradable component for an oral colon delivery system based on a combination strategy: formulation and in vitro evaluation - Saliha Moutaharrik; Gabriele Meroni; Alessio Soggiu; Anastasia Foppoli; Matteo Cerea; Luca Palugan; Francesca Caloni; Piera Anna Martino; Andrea Gazzaniga; Alessandra Maroni (Drug Delivery and Translational Research, 2024)

Replacement of animal testing by integrated approaches to testing and assessment (IATA): a call for in vivitrosi - Francesca Caloni; Isabella De Angelis; Thomas Hartung (Archives of Toxicology, 2022)
Alternative methods to animal use in toxicology are evolving with new advanced tools and multilevel approaches, to answer from one side to 3Rs requirements, and on the other side offering relevant and valid tests for drugs and chemicals, considering also their combination in test strategies, for a proper risk assessment. While stand-alone methods, have demonstrated to be applicable for some specific toxicological predictions with some limitations, the new strategy for the application of New Approach Methods (NAM), to solve complex toxicological endpoints is addressed by Integrated Approaches for Testing and Assessment (IATA), aka Integrated Testing Strategies (ITS) or Defined Approaches for Testing and Assessment (DA). The central challenge of evidence integration is shared with the needs of risk assessment and systematic reviews of an evidence-based Toxicology. Increasingly, machine learning (aka Artificial Intelligence, AI) lends itself to integrate diverse evidence streams. In this article, we give an overview of the state of the art of alternative methods and IATA in toxicology for regulatory use for various hazards, outlining future orientation and perspectives. We call on leveraging the synergies of integrated approaches and evidence integration from in vivo, in vitro and in silico as true in vivitrosi.

Metal content in the liver, kidney, and feathers of Northern gannets, Morus bassanus, sampled on the Spanish coast - Veronica Nardiello; Luis Eusebio Fidalgo; Ana López-Beceiro; Alessia Bertero; Salomé Martínez-Morcillo; María Prado Míguez; Francisco Soler; Francesca Caloni; Marcos Pérez-López (Environmental Science and Pollution Research, 2019)

Reference intervals for B-esterases in gull, Larus michahellis (Nauman, 1840) from Northwest Spain: influence of age, gender, and tissue - Salomé Martínez Morcillo; Maria Chiara Perego; Jorge Vizuete; Francesca Caloni; Cristina Cortinovis; Luis Eusebio Fidalgo; Ana López-Beceiro; María Prado Míguez; Francisco Soler; Marcos Pérez-López (Environmental Science and Pollution Research, 2018)

Lead, cadmium and organochlorine pesticide residues in hunted red deer and wild boar from northern Italy - Mario Chiari; Cristina Cortinovis; Marco Bertoletti; Loris Alborali; Mariagrazia Zanoni; Enrica Ferretti; Francesca Caloni (Food Additives & Contaminants: Part A, 2015)